Penerapan Mind Mapping Sebagai Metode Meningkatkan Skill Berpikir Kritis Peserta Didik di Sekolah Dasar - Arsita, Sofia Inov Putri Arsita; Choiriyah (Jurnal Penelitian Pendidikan, 2024)
This research was conducted after the researcher carried out observation activities in the fourth grade of SD Muhammadiyah 23 Surakarta. The researcher found that in their study, the level of critical thinking in the IPAS subject of the fourth-grade students was still considered low. This can be proven by the learning outcomes, which are still below average. This study aims to improve the critical thinking skills of students in the IPAS subject through the application of the mind mapping method. The research method used is Classroom Action Research (CAR), which was conducted in two cycles. The research results show an increase in each cycle. In the pre-cycle, the average class score was 5.76 with a percentage of 64%. In Cycle I, the average class score became 7.24 with a percentage of 80.4%. Then, in Cycle II, the average class score became 7.96 with a percentage of 88.4%. This indicates an improvement in each cycle, with Cycle I showing an increase of 16.4% and Cycle II showing an increase of 8% from the previous cycle. Based on the research that has been conducted, it can be concluded that the mind mapping method can improve the critical thinking skills of students in the IPAS subject in the fourth grade of elementary school.